Accuracy Of The Results Of Scientific Research On An Autonomous Voltage Inverter (Eurasian Journal of Engineering and Technology, 2026)
This article examines the reliability of scientific research results on improving the energy characteristics and efficiency of a stand-alone inverter. The study also analyzes the correlation between the reliability of these results and variations in the inverter's input voltage range.